EKSPRESI TOPENG - Ms. Parjiyah (SURYA SENI, 2009)
Expression of Mask. Mask Art represent is one of the cultural heritage result of Indonesian nation there is since long time and continued till now. Mask art have the symbolic value of characterization human being as according to teaching moral-etic. Symbolic value look at concept of face forming from mask with the colour cloth. Visual aesthetic method formulation from meaningful mask art of characterization symbolism is played by every ﬁ gure.  Mask very interesting to made the source of inspiration of textile creation. Starting frombackground and idea which explained above, writer aim to to create the artistic textile in the form of valuable mask of decorative, unique, artistic, and ethnic. Base on text above, writer want to create textile creation two and three dimensional from the source of idea form the mask that made by assorted of mask expression. Process the making of this creation through three step and that are exploration that have source from idea of scheme and materialization through the creative new planning of inovatif creation The substance is used are the some kind media, hutch, agel, glass, brass, wood, shell of coconut withmacrame technique. In materialization more emphasizing of personal expression without leaving meaning and message which implied in the source of creation idea. The realization of art creations is not only concerning of visual beauty butalso meaning and ﬁ ll the masterpiece.Through the process from the creation idea or accomodating the writer’s desire in creating the art creation. This creation is expected can be the one effort to preserve in society. Folk art must be interpreted by a alertness to prevent of thestabilization of tradition development suitable to demand from new culture.Keywords : expression, mask, and makrame.